High levels of erythropoietin are associated with protection against neurological sequelae in African children with cerebral malaria. - Casals-Pascual, C; Idro, R; Gicheru, N; Gwer, S; Kitsao, B; Gitau, E; Mwakesi, R; Roberts, D; Newton, C (2008)
Cerebral malaria (CM) in children is associated with a high mortality and long-term neurocognitive sequelae. Both erythropoietin (Epo) and vascular endothelial growth factor (VEGF) have been shown to be neuroprotective. We hypothesized that high plasma and cerebrospinal fluid (CSF) levels of these cytokines would prevent neurological sequelae in children with CM. We measured Epo, VEGF, and tumor necrosis factor in paired samples of plasma and CSF of Kenyan children admitted with CM. Logistic regression models were used to identify risk and protective factors associated with the development of neurological sequelae. Children with CM (n = 124) were categorized into three groups: 76 without sequelae, 32 with sequelae, and 16 who died. Conditional logistic regression analysis matching the 32 patients with CM and neurological sequelae to 64 patients with CM without sequelae stratified for hemoglobin level estimated that plasma Epo (>200 units/liter) was associated with >80% reduction in the risk of developing neurological sequelae [adjusted odds ratio (OR) 0.18; 95% C.I. 0.05-0.93; P = 0.041]. Admission with profound coma (adjusted OR 5.47; 95% C.I. 1.45-20.67; P = 0.012) and convulsions after admission (adjusted OR 16.35; 95% C.I. 2.94-90.79; P = 0.001) were also independently associated with neurological sequelae. High levels of Epo were associated with reduced risk of neurological sequelae in children with CM. The age-dependent Epo response to anemia and the age-dependent protective effect may influence the clinical epidemiology of CM. These data support further study of Epo as an adjuvant therapy in CM.